Synthesis and characterization of naphthalene diimide polymers based on donor-acceptor system for polymer solar cells - S. Chen; Q. Xu; J. Wang; W. Li; H. Wang (eXPRESS Polymer Letters)
Three donor-acceptor (D–A) naphthalene diimide copolymers, poly{thieno[3,2-b]thiophene-diyl-alt-N,N'-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)}(P1), poly{4,8-dioctyloxybenzo[1,2-b;3,4-b']dithiophene-diyl-alt-N,N!-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)}(P2), and poly{4,8-bis(2-ethylhexyloxy)benzo[1,2-b:4,5-b']dithiophene-diyl-alt-N,N'-bis(2-octyldodecyl) -naphthalene-1,4,5,8-bis(dicarboximide)}(P3), were synthesized by Stille coupling reaction. All copolymers showed good solubility in common organic solvents with broad absorption region and narrow optical band gap. The electrochemical properties of the polymers can be adjusted by changing the donor segment. P1 showed n-type characteristic while P2 and P3 showed p-type characteristic. All-polymer solar cells using P3HT as the donor and P1 as the acceptor were fabricated and the highest power conversion efficiencies (PCEs) of 0.068% were obtained under the preliminary condition. Moreover, p-type naphthalene diimide copolymers (P2 and P3) based on D–A system were used as donors to fabricate bulk heterojunction polymer solar cells (BHJ, PSCs) for the first time, and the maximum power conversion efficiencies PCEs were about 0.021 and 0.017%, respectively.